Gender Differences in Physical Performance and Psychological Assessment Among Cuban National Athletics Team - Feria-Madueño, Adrián (2024)
Introduction: Elite sports pose potential health risks, but are vital to the well-being of society. In Cuban society, sport is an integral part of personal development and public health, fostering unity and promoting female participation for sustainable growth. Athletics is one of the most important sports in Cuban sport, and should be approached both from the point of view of sports training and sports psychology. Purpose: The aim of this study was to provide a description of conditional variables in a countermovement jump (CMJ), mood profile, self-efficacy, and the leg-hip height index among athletes from the Cuban national athletics pre-selection team, differentiated by gender. Methods: Our sample consisted of the Cuban national athletics pre-selection team. Results: Mood profile analysis using the Profile of Mood States (POMS) did not reveal significant gender differences, with a small effect size for gender. Men showed a slightly greater trend towards vigor compared to women. Significant differences in self-efficacy were observed between men and women in their confidence levels to achieve jump heights between 21 and 40 cm using the CMJ. However, no significant differences were found for jumps exceeding 40 cm, highlighting the importance of strategies to enhance athletes’ psychological needs and self-efficacy. Conclusions: This study suggests that the association between tension-related anxiety and performance indicators related to jump height may play a crucial role in determining specific profiles in male and female Cuban athletes. Our comprehensive analysis contributes to understanding gender differences in performance factors. These findings provide valuable insights for future research and athlete development strategies.